Necessity and other-defence - Eggert, L (Columbia University, 2024)
This paper examines the necessity requirement in cases in which more than one defensive agent could avert the same threat of harm. It argues that the most compelling view of necessity is one that seeks to minimize harms by extending the constraint across agents pursuing the same defensive aim. Whether it is necessary, and to that extent permissible, for one agent to use defensive force may depend on whether another agent is likely to avert the same threat in a less harmful manner. This conception of necessity, however, seeks only to minimize harms in pursuit of a specific aim; it does not tell us which one of several ends to pursue based on how harmful different acts of rescue would be. This throws new light on the ethics of using defensive force in situations in which agents do not act alone.